Blood pH and lactate kinetics in the assessment of running endurance - Usaj, A.; Starc, V. (International Journal of Sports Medicine, 1996)
To study how two types of testing protocols for the determination of the [LA] and blood pH kinetics during running match each other, a group of nine runners participated in two testing protocols. The first protocol consisted of a sequences of 8 x 2000 m runs at constant speed, which was increased on different testing days. The first protocol was used for the determination of running speed (v), [LA], pH and heart rate (HR) corresponding to the Lactate Threshold (LT) and the Threshold of Acidosis (TA), both occurring at similar running speeds (4.21 +/- 0.44 and 4.22 +/- 0.40 m/s) (mean +/- SD) and HR (159 +/- 7 and 160 +/- 9 1/min), [LA] = 2.0 +/- 0.6 mmol/l and pH = 7.411 +/- 0.018. Maximal steady values for [LA] (maxLAss) and minimal steady values for pH (minpHss) obtained by the second protocol were higher (p < 0.01) according to running speed (4.62 +/- 0.38 and 4.66 +/- 0.38 m/s), HR (172 +/- 7 and 174 +/- 8 1/min) and [LA] (5.7 +/- 1.3 mmol/l) and lower according to pH (7.364 +/- 0.021), respectively. Unlike similar running speeds determined by LT and TA, the minimal steady pH level occurred at a slightly higher speed than the speed at maxLAss. Additionally, we found a drift of pH towards a resting level, when [LA] fluctuated around a steady level. Furthermore, the parameters of pH kinetics correlated better with the running speed of the 4000 m run that was taken as the parameter of short endurance performance, than those of [LA] kinetics. We conclude that these differences in [LA] and pH kinetics could serve to predict the capabilities of runners with respect to the two endurance performance types: long and short.